PELATIHAN BAHASA INGGRIS DENGAN METODE BELAJAR 2C UNTUK SISWA PROGRAM PAKET C SETARA SMA IPS DI SANGGAR KEGIATAN BELAJAR (SKB) PURWOKERTO - Benny Krisbiantoro; Alfizi .; Tri Pujiani (PUSAT PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT, POLITEKNIK KESEHATAN KEMENTERIAN KESEHATAN PALEMBANG, 2021)
Sanggar Kegiatan Belajar is one of the non-formal and informal educational institutions (PNFI) that organizes learning activities for the equivalency program. The problem that occurs in Purwokerto SKB is that the age of the learning citizens in a study group is various, each has different needs so that the sustainability of the program is difficult to maintain. Heterogeneous input of students and most of them come from the lower middle economic class and including families of recipients of the PKH program from the government is also one of the triggers for problems in learning. In addition, the absence of English language training is one of the problems that occur in SKB considering that English can be used as a plus point for students to get a job. The English language skills of the Paket C (SMA Equivalent) equivalency program students are still very low as evidenced by the average score of the final even semester test for the 2018/2019 academic year, which is 56.17 and the average score of UNBK in 2018 was 34.19. The lack of facilities and infrastructure that support the teaching and learning process of English is part of the causes of students' low English proficiency apart from input factors, student characteristics, interest and student motivation to learn. The use of learning methods that are fun, interactive, exploratory, systematic, creative and innovative is very helpful in improving students' English skills. The 2C method is a combination of two methods, namely the cooperative learning method and the contextual teaching and learning method. In this Community Partnership Program, the 2C method was used to train Paket C program students in improving their English language skills. Moreover, this Community Partnership Program was aimed to provide training to students in increasing their interest and motivation to learn English. The result of the training revealed that there was a significant improvement in students’ learning interest and motivation as well as their English performance.